Structural Understanding of Interleukin 6 Family Cytokine Signaling and Targeted Therapies: Focus on Interleukin 11 - Metcalfe, Riley D.; Putoczki, Tracy L.; Griffin, Michael D. W. (Frontiers in Immunology, 2020)
Cytokines are small signalling proteins that have central roles in inflammation and cell survival. In the half-century since the discovery of the first cytokines, the interferons, over fifty cytokines have been identified. Amongst these is interleukin (IL)-6, the first and prototypical member of the IL-6 family of cytokines, nearly all of which utilise the common signalling receptor, gp130. In the last decade, there have been numerous advances in our understanding of the structural mechanisms of IL-6 family signalling, particularly for IL-6 itself. However, our understanding of the detailed structural mechanisms underlying signalling by most IL-6 family members remains limited. With the emergence of new roles for IL-6 family cytokines in disease and, in particular, roles of IL-11 in cardiovascular disease, lung disease, and cancer, there is an emerging need to develop therapeutics that can progress to clinical use. Here we outline our current knowledge of the structural mechanism of signalling by the IL-6 family of cytokines. We discuss how this knowledge allows us to understand the mechanism of action of currently available inhibitors targeting IL-6 family cytokine signalling, and most importantly how it allows for improved opportunities to pharmacologically disrupt cytokine signalling. We focus specifically on the need to develop and understand inhibitors that disrupt IL-11 signalling.